Implementasi Dial-In Server Menggunakan PPPD Dengan Sistem Operasi Linux - Fatchur Rochim, Adian (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Some of the preliminary preparation of the necessary specification is hard to support the device to perform the installation of dial up and dial in connection with the PPP protocol and CSLIP. Interconnection need hardware support with Serial port from dial up client, PCI/ISA Slot for modem card or USB port for connection with Handphone. interconnection hardware is needed on the client and the server is available Serial port (for external modem), PCI / ISA card for the modem and / or USB port for connection with cable data Handphone. This method useful for admin network for maintain his network from remote area.Keywords: Dial Up server, Connection USB, Connection Handphone